IL-15 in the Combination Immunotherapy of Cancer - Waldmann, Thomas A.; Dubois, Sigrid; Miljkovic, Milos D.; Conlon, Kevin C. (Frontiers in Immunology, 2020)
We completed clinical trials of rhIL-15 by bolus, subcutaneous, and continuous intravenous infusions (CIV). IL-15 administered by CIV at 2 mcg/kg/day yielded a 38-fold increase in 10- day number of circulating NK cells, a 358-fold increase in CD56bright NK cells and a 5.8-fold increase in CD8 T cells. However, IL-15 preparations administered as monotherapy were ineffective, due to actions of immunological checkpoints and due to the lack of tumor specific targeting by NK cells. To circumvent checkpoints, trials of IL-15 in combination with other anticancer agents were initiated. Tumor-bearing mice receiving IL-15 with antibodies to CTLA-4 and PD-L1 manifested marked prolongation of survival compared to mice receiving IL-15 with either agent alone. In translation, a phase I trial was initiated involving IL-15 (rhIL-15), nivolumab and ipilimumab in patients with malignancy (NCT03388632). In rhesus macaques CIV IL-15 at 20 μg/kg/day for 10 days led to an 80-fold increase in number of circulating effector memory CD8 T cells. However, administration of γc cytokines such as IL-15 led to paralysis/depression of CD4 T-cells that was mediated through transient expression of SOCS3 that inhibited the STAT5 signaling pathway. This lost CD4 helper role could be restored alternatively by CD40 agonists. In the TRAMP-C2 prostate tumor model the combination of IL-15 with agonistic anti-CD40 produced additive effects in terms of numbers of TRAMP-C2 tumor specific Spas/SCNC/9H tetramer positive CD8 T cells expressed and tumor responses. A clinical trial is being initiated for patients with cancer using an intralesional anti-CD40 in combination with CIV rhIL-15. To translate IL-15-mediated increases in NK cells, we investigated combination therapy of IL-15 with anticancer monoclonal antibodies including rituximab in mouse models of EL-4 lymphoma transfected with human CD20 and with alemtuzumab (CAMPATH-1H) in a xenograft model of adult T cell leukemia (ATL). IL-15 enhanced the ADCC and therapeutic efficacy of both antibodies. These results provided the scientific basis for trials of IL-15 combined with alemtuzumab (anti-CD52) for patients with ATL (NCT02689453), with obinutuzumab (anti-CD20) for patients with CLL (NCT03759184), and with avelumab (anti-PD-L1) in patients with T-cell lymphoma (NCT03905135) and renal cancer (NCT04150562). In the first trial, there was elimination of circulating ATL and CLL leukemic cells in select patients.